Low complexity adaptive MIMO-OFDM system for transmission under correlated frequency-selective channels - Halmi, Mohd Hairi; Abenoh, Mohd Zammahsyari; Mat Desa, Shahbe; Ibrahim@Ghazali, Siti Azlida; Hafiza, W. H.; Diyana, W. M. (IEEE Xplore, 2005)
Existing works on MIMO systems have been restricted to either uncorrelated frequency-selective channels or correlated non frequency-selective channels. Practical MIMO systems however, suffers from the effects of frequency selectivity and channel correlation due to the high transmission rate and proximity of the transmit antennas. This paper presents a low complexity adaptive MIMO-OFDM system. The system exploits the time, frequency and spatial dimensions to provide high data rate and robust signal transmission in frequency selective channels with varying correlation levels. Compared to existing MIMO-OFDM systems, the proposed system provides up to 2-3 dB gains under low channel correlations and more than 5 dB gains in highly correlated channel.